Outpatient Drug Cost Containment in Civil Servant Medical Benefit Scheme : Lessons from Lampang Hospital - Yingseree, Boonyaporn (Journal of Health Science of Thailand, 2017)
Outpatient expenditures in civil servant medical benefit scheme increased rapidly after changing outpatient reimbursement system by direct payment from the Controller General’s department (CGD). Lampang hospital, one among 34 hospitals were assigned to develop and implement outpatient drug cost containment measures. The objective of this pre-post intervention study was to evaluate effectiveness of the drug cost containment measures comprised of generic substitution, restricted formulary management to ensure rational use of target drugs, clinical practice guideline developed by physician to promote therapeutic substitution of essential drugs, medication utilization analysis and drug cost awareness carried out by pharmacists. Drug expenditure data was collected between October to July in fiscal year 2009 and 2010 in order to compare total outpatient drug expenditures, non essential drug cost, propotion of 7 target target drug groups, proportion of non essential drug cost of target drug groups. It was shown that after containment measures in place, total out-patient drug expenditure decreased by 30.62 million baht (24.9%), non essential drug (NED) cost by 19.85 million baht (25.0%), NED cost of target drug groups by 17.48 million baht (45.45). While the propotions of 7 target drug groups were reduced by 5.56 percent, proportions of NED cost of 6 target drug groups besides drugs for bone metabolism: chemotherapy, proton pump inhibitors, angiotensin II receptor blocker, statins, drugs for chronic hepatitis, NSAIDs and glucosamine by 34.2, 26.0, 22.9, 11.0, 5.7 and 0.5 percent respectively. In conclusion, this study showed that decisive drug cost containment policy, multidisciplinary approach to promote rational use of drug, medication utilization analysis, periodically monitoring prescribing pattern and drug cost awareness could reduce outpatient drug expenditure and non essential drug cost in fiscal year 2010.